THE EFFECT OF USE OF RATION RICE BRAND FERMENTED ON THE PHYSICAL AND CHEMICAL QUALITY OF KAMPONG UNGGUL BALITNAK (KUB) - Emy Saelan; Sulasmi (Fakultas Pertanian Universitas Majalengka, 2022)
The research was conducted with the with the of knowing the effect of fermented rice brand in the ration on the physical and chemical quality of Kampung Unggul Balitnak (KUB) chicken meat the age of 12 weeks. The study used a Completed Randomized Design (CRD) with 5 treatments and 4 replications and each replication consisted of 5 KUB chickens. The treatment in the study were: R0 (control); P1 (90% control + 10% fermented brand); P2 (80% control + 20% fermented brand); P3 (70 control + 30% fermented brand); P4 (60% control + 40% fermented brand). The treatment ration was given to KUB chickens aged 1 (one) week until the age of 12 weeks, after which they were slaughtered for analysis of the physical and chemical quality of chicken meat. The results showed that the use of fermented rice brand in the ration showed significantly different results (P<0,05) on the physical and chemical quality of KUB chicken meat. This shows that the provision of fermented rice brand up to 40% in the KUB chicken rations is recommended.